Non-adherence to psychiatric medication in adults experiencing homelessness is associated with incurred concussions - Rangu, Neal; Frank-Pearce, Sumer G.; Alexander, Adam C.; Hébert, Emily T.; Ra, Chaelin; Kendzor, Darla E.; Businelle, Michael S. (Frontiers in Human Neuroscience, 2022)
This study investigated the relationship between concussions and medication adherence among 247 adults experiencing homelessness in Oklahoma City, Oklahoma, who were prescribed medication for a psychiatric disorder. Participants were asked whether they had “ever experienced a blow to the head that caused a concussion,” and medication adherence was measured by asking participants whether they had taken their psychiatric medication yesterday. The data were analyzed using univariate and multivariable logistic regressions. Results showed that more than half of the sample had a concussion history (61.9%), and homeless adults with a concussion history had higher odds of non-adherence to psychiatric medications compared with those who reported no concussion history (OR = 2.13 [95% CI = 1.08, 4.18]). Findings suggest that concussions may be associated with medication non-adherence. Raising awareness among service providers of the relationship between traumatic brain injury and medication adherence may increase efforts to improve adherence in this underserved population.